A STUDY ON CAUSES OF KNITTING MACHINE STOPPAGES AND THEIR IMPACT ON FABRIC PRODUCTION - Reza, Mohammad Hosain; Hossain, Md. Kamal (European Scientific Journal, ESJ, 2015)
Knitting machine stoppages cause loss of fabric production. The smooth running of knitting machine depends on yarn quality, knitting machine conditions and knitting production conditions. Knitting machine stops due to different causes. In this work it was found that the causes of stoppages are yarn breakages, set-off, machine cleaning and fabric roll cutting, yarn joining, needle breakages and oil problem. The major cause of knitting machine stoppage was machine cleaning and fabric roll cutting. It occupies almost 40.38% of total stoppage time. This cause lead to the production loss of 43.48 kg of fabric. Similarly, yarn breakages, set-offs, and other causes like yarn joining and needle breakages occupied 20.19%; 7.69% and 31.7% of total stoppage time respectively. The knitting machine was stopped for total 312 minutes among 24 hours or 1440 minutes of running due to all of the causes. The causes, combindly led to production loss of 107.66 kg of fabric in 24 hours. Due to the all of the causes total 21.66% of fabric production loss was realized.